The Influence of Parasocial Interaction on Purchase Intention Through Value Perception: Study on Local Clothing Brands in Indonesia - Anwarsyah, Difi; Rifa, Hudzaifah; Robian, Rio; Ananda, Mochammad; Rahayu, Fatik (Manunggal Halim Jaya, 2025)
The fashion industry in Indonesia is experiencing rapid growth, particularly with the rising popularity of local clothing brands. In the digital era, social media influencers play a pivotal role in marketing through Parasocial Interactions (PSI), which can significantly shape consumers' perceived value and purchase intention. This study examines the influence of influencers' Social Attractiveness and Physical Attractiveness on Parasocial Interactions, and how these interactions affect perceived Social Value, Personal Value, and ultimately, purchase intention for local clothing brands. A quantitative research approach was employed using Structural Equation Modeling (SEM). Data were collected through a survey distributed to social media users who follow influencers and have prior experience purchasing local fashion products. The findings reveal that both Social Attractiveness and Physical Attractiveness of influencers have a positive and significant effect on Parasocial Interactions. Furthermore, parasocial interactions significantly enhance perceived social and personal values, leading to higher purchase intention among consumers.